Modeling of the BEAM robot control systemon the basis of a microcircuit L293D - Yevsieiev, V. (My University, 2023)
This work is devoted to the modeling and implementation of the BEAM control circuit of a phototaxis robot (directed movement towards or away from light). To implement control systems, the author uses the L293D microcircuit with minimal wiring. As a result of the modeling carried out in the Autodesk Tinkercad environment, a circuit was developed that implements the movements of the BEAM robot in the direction of light, while the implementation of the control program is built on the basis of logical elements, without the use of program code, which makes the BEAM robot reliable and durable.
Keywords: BEAM; robotics; caravan systems; phototaxis